Mediterranean sheep and goats production: An uncertain future - de Rancourt, M.; Fois, N.; Lavín, M. P.; Tchakérian, E.; Vallerand, F. (Small Ruminant Research, 2006)
European sheep and goat production, in the Mediterranean areas represent important economic, environmental and sociological issues. Our article aims at comparing the situation of the main small ruminant systems in South European regions (Spain, France, Italy and Greece), and their possible future evolution. On the average, the income of milk systems tends to be higher than meat systems thanks to a good market price. Moreover, the dependence on subsidies is greater in meat systems and in extensive systems. However, milk systems seem more sensitive to the market situation for example, Italian products in the USA and products from Greece with respect to certain foreign companies. Sheep and goat production, being frequently the only possible enterprises in less favoured areas, are often fundamental to maintaining social activities and to keep the vegetation out of danger from fire. However, in Greece and Spain some intensive systems are becoming established in the more fertile plain areas. The roads to success are rather uncertain considering the new CAP reform as nearly all these systems seem to be dependent on the important European subsidies. Nevertheless, we have identified different ways to progress according to systems and regions. Such an uncertain future could be easier to forecast if those involved in the sheep and goat sectors worked more collectively in Europe.
Keywords: EUROPE; Goat; mediterranean countries; production; Sheep